The role of the Rural Improvement Clubs of Bulacan in the promotion of the adult education program in the Philippines - Bernardino, Felicita (Gonzales) 1918- (1961)
Many organizations sponsor adult education programs. Among these organizations is the Rural Improvement Clubs (RIC) of the Philippines which is the subject of this investigation. This special problem attempts to determine the role of the Rural Improvement Clubs of Bulacan in the promotion of the Adult Education Program in the Philippines. In order to find out this role, the investigation gives in detail, the objectives, areas of work, program of activities and methods of implementation of the Adult Education Division of the Bureau of Public Schools and likewise that of the Rural Improvement Clubs of the Philippines and of Bulacan in particular.
Thesis (M.Ed.)--University of the Philippines, 1961.
Keywords: Rural Improvement Clubs of the Philippines; Education of adults